REGULATORY DYNAMICS IN PEER-TO-PEER LENDING: A COMPARATIVE STUDY OF INDONESIA, SINGAPORE, AND AUSTRALIA - Puspita, Viona; Amboro, Florianus Yudhi Priyo; Syarief, Elza (Universitas Syiah Kuala, 2024)
The growth of peer-to-peer lending requires robust legal regulations to protect stakeholder rights and facilitate continued economic development in Indonesia through enhanced access to funding. This article seeks to analyze the legal developments surrounding peer-to-peer lending in Indonesia, Singapore, and Australia. Utilizing a doctrinal legal research methodology with a comparative approach, the findings reveal that Singapore and Australia can effectively leverage existing regulations without the need to create new ones, thereby mitigating the risk of legal dissonance. In contrast, while Indonesia has implemented specific regulations for peer-to-peer lending, it has not provided sufficient normative legal protection within this sector and has failed to safeguard the rights guaranteed by those regulations. These findings suggest that a specific regulatory approach may not be the most effective strategy for Indonesia's legal development, thereby contributing to the ongoing discourse surrounding legal advancements in the fintech industry.How to CiteViona Puspita et. al. (2024). Regulatory Dynamics In Peer-To-Peer Lending: A Comparative Study Of Indonesia, Singapore, And Australia. Kanun: Jurnal Ilmu Hukum, 26(3), 467-487. https://doi.org/10.24815/kanun.v26i3.37392